ACCESSORY MENTAL FORAMINA: A RADIOLOGICAL ASSESSMENT OF THREE CASES - Andrei Leonid Chirita; Teodora Matei (Romanian Society of Oral Rehabilitation, 2020)
The accessory mental foramen (AMF) is an anatomical variant seen in up to 14% of patients. When present, its location may influence the surgical approach on the lateral surface of the mandible in order to avoid its neurovascular content. This article presents three cases diagnosed with AMF and discuss the clinical implications of these foramina.